The Relationship between Organizational Forgetting With organizational Innovation and organizational Agility Among the Employees of Isfahan Education Organization - MOHAMAD REZA HOJATI NAJAFABADI; Mahboubeh Sadat Fadavi (Allameh Tabataba'i University Press, 2017)
The persent study investigated the relationship between Organizational Forgetting With organizational Innovation and Organizational Agility was conducted in Isfahan Education Statistical reserch, education and community organizations Isfahan city that consisted of 450 patients .Based on sample size Kertesi and Morgen(1970) , 207 stratified random sampling methods were use for . Searching tools of Salavati et al Organizational Forgetting Questionnaire (1392) , with 17 items , Esmaeil et al Organizational Innovation Questionnaire (2002), with 33 items and Sharifi and Jang Organizational Agility Questionnaire (2004) , with 29 items colleagues validity was confirmed by experts Management of reliability using Chrobak were for Intentional and Accidental Organizational Forgetting Questionnaire (97% ,79%) , organizational Innovation Questionnaire(84%) , organizational Agility Questionnaire(77%) and zero persent is calculated . Using version 22 of statistical package in social sciences (SPSS) , the analysis of this research was done in two levels of descriptive and inferential statistics .The results showed that there is a significant relationship between Intentional Organizational Forgetting with organizational Innovation(r= 0/37 ,p<0/05 ) and there is a significant inverse relationship between Accidental Organizational Forgetting with organizational Innovation (r= -0/14 ,p<0/05 ) . There is a significant relationship between Intentional Organizational Forgetting with organizational Agility(r=0/41 ,p<0/05 ) ,but between Accidental Organizational Forgetting with organizational Agility were not significant .Results showed the best predictor of organizational Innovation is Intentional Organizational Forgetting, and only predictor of Agility organizational was Intentional Organizational Forgetting .